Effects of acute physical fatigue on gaze behavior in expert badminton players - Taupin, M. L.; Ruffault, A.; Slawinski, J.; Bayle, D. (Journal of Sport & Exercise Psychology, 2024)
Perceptual cognitive skills in real game settings, under conditions of fatigue, such as the ability to gather relevant visual information, are key factors in achieving motor goals in sports. The objectives were to evaluate the effects of acute physical fatigue on gaze behavior during a badminton game (Study 1) and in an unfavorable force ratio situation (Study 2). Six international-level badminton players played two sets and unfavorable force ratio situations while wearing eye-tracking glasses before and after a fatiguing task. During the set, fatiguing physical exercise led to fewer fixations per exchange and more fixations on one area of interest. During unfavorable force ratio situations, fatiguing physical exercise led to shorter fixation durations per exchange, shorter fixation durations on two areas of interest, and longer fixation durations on one area of interest. The results showed that gaze behaviors were adapted in acute physical fatigue conditions to maintain performance.